Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Usahatani Durian di Desa Garuda Kecamatan Padangguni Kabupaten Konawe - Anugrah Anugrah; La Karimuna; Mursal Junus (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2024)
The objective of this study is to analyze the income of durian farmers (Durio zibethinus Murr.) and to examine the influence of these production factors on the income of durian farmers in Garuda Village, Padangguni Subdistrict, Konawe District. This research was conducted in Garuda Village, Padangguni Subdistrict, Konawe District from May to June 2024. The population in this area consists of 30 farmers, thus a saturated sampling technique or census. The analysis methods used are income analysis and Multiple Linear Regression. The results of this study show that the average income obtained by durian farmers is Rp. 50,972,983/Ha/season. Based on the F-test, the variables of land area, number of trees, selling price, and labor wages significantly affect the dependent variable. The T-test indicates that the variables of land area, number of trees, and selling price significantly and positively affect the income of durian farmers in Garuda Village, Padangguni Subdistrict, Konawe District. In contrast, labor wages have a negative effect related to age, where younger labor tends to increase production results, while older labor results in decreased production due to declining physical abilities, thus affecting the income received.